Surto de varicela em creches e escolas da Direção Regional de Saúde XXII, junho de 2005 - Guedes Pellini, Alessandra; Frugis Yu, Ana Lúcia; Oliva Sidi, Maria Stella; Marques Pinto Carvalhanas, Telma Regina; Vilaça, Pedro José; Madalosso, Geraldine (BEPA. Boletim Epidemiológico Paulista, 2005)